The Role of Strategic Planning During the Establishment of Syferfontein Colliery (The Australasian Institute of Mining and Metallurgy, 1992)
Syferfontein Colliery, part of the Sasol group of companies which specialises in the field of petro-chemical production, was established in 1990. The mine is situated about 150 km east of Johannesburg, South Africa. Two coal seams are mined, utilising two 75 m3 draglines, shovels and a fleet of 177 ton rear dump trucks. The mine will reach its full production capacity of seven million tonnes per annum in 1992. During the planning period, prior to the establishment of the mine, management were confronted with the unstable socio-political environment in South Africa which could jeopardise the eventual success of the mine. They consequently conducted a strategic planning exercise to determine guidelines for mine planning to improve the chances of success in this unstable third world environment.The strategic guidelines formed the basis for specific actions taken during the planning and commissioning of the mine. Specific actions were taken in the field of operating cost, labour relations, working environment, logistics and the general environment. First results indicate that these actions have played a major role in the success of the mine to-date. This process can be utilised by others facing similar or even totally different uncertainties.